KORELASI KADAR FERITIN DENGAN HEMOGLOBIN PADA PENDERITA ANEMIA PASCA VAKSIN COVID – 19 - nugroho nug tristyanto; Marufah (LPPM Universitas Abdurrab, 2025)
Anemia is a condition in which the mass of erythrocytes and/or circulating hemoglobin does not fulfill its function to provide oxygen. This is due to a decrease in the number of erythrocytes which is often reported as a decrease in hemoglobin concentration for body tissues. Decreased ferritin levels are a marker of iron deficiency. Increased ferritin levels are a marker of metastatic carcinoma, leukemia, lymphoma, liver disease (cirrhosis, hepatitis, liver cancer), excess iron (hemochromatosis), hemosiderosis, anemia (hemolytic, pernicious, thalassemia), infection, chronic and acute inflammation (kidney disease, neuroblastoma), and tissue damage. The study aims to determine the Correlation of Ferritin Levels with Hemoglobin in Patients with Anemia After the Covid-19 Vaccine. This study method is observational with a cross-sectional approach. From the results of testing with SPSS Normality Test, the P value or significance of Kolmogorov-Smirnov from Ferritin and hemoglobin levels> hemoglobin 0.00 is obtained. This means it is smaller than the significance level (α) of 0.05, and means the data is not normally distributed. The correlation analysis of ferritin and h tested with Spearman correlation due to non-normal distribution obtained a sig value of 0.001 <0.05, thus this means H1 is accepted. And based on the Correlation Coefficient value obtained a value of 0.578, which means it has a moderate correlation. Based on the results of this study, it can be concluded that there is a relationship between ferritin levels and hemoglobin in anemia sufferers.Keywords: Ferritin, anemia, Covid-19 Vaccine